Saprotrophic litter fungi in a Mediterranean ecosystem: Behaviour on different substrata - Pasqualetti, M; Mulas, B; Rambelli, A; Tempesta, S (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
Saprotrophic fungi sporulating on 17 types of leaf litter collected during the dry season in the Sardinian Mediterranean area were analysed. The fungal assemblages identified in each substratum showed an overlap value ranging from 5.9 to 46.7%. A consistent connection between certain fungal species and their substrata was detected; among the 168 fungal species identified, 104 (62%) may be regarded as specialised. Each fungal species was characterised according to morphological and ecological features. Multidimensional scaling (MDS) showed that ubiquitous and common species have morphological characters distinguishing them from specialised species.
doi: 10.1080/11263504.2013.877534
Keywords: litter decomposition; Mediterranean ecosystem; saprotrophic fungi

Mediterranean natural forest living at elevated carbon dioxide: soil biological properties and plant biomass growth - Moscatelli, M C; Fonck, M; De Angelis, P; Larbi, H; Macuz, A; Rambelli, A; Grego, S (Soil Use and Management, 2001)
Abstract. Biomass productivity and soil microbial responses to long-term CO2 enrichment have been investigated in a Mediterranean natural forest ecosystem. Several biochemical parameters have been measured on soil samples taken from six open top chambers (OTCs), enclosing clumps of natural Mediterranean woody vegetation including: Quercus ilex L., Phillyrea angustifolia L., Pistacia lentiscus L. and Myrtus communis L. The CO2 concentration of the air inside the OTCs was either ambient or ambient plus 350 μmol mol–1 (c. 710 ppm as mean daily value). Microbial C biomass, microbial respiration, dehydrogenase, β-glucosidase, acid phosphatase and protease activities, inorganic N and soluble P, were tested in order to evaluate soil microbial size and activity. Statistically correlated seasonal patterns have been identified in some biochemical parameters in response to climatic conditions, soil nutritional status and the physiology of the vegetative cover. In situ soil respiration and above- and below-ground productivity were also measured. Microbial responses to CO2 enrichment were observed only at the beginning of the study and a general progressive reduction of the CO2 effect was recorded as monitoring continued. These results are in agreement with data from literature regarding similar studies on natural complex communities.
Keywords: Carbon dioxide; Forests; Mediterranean Region; microbial activities; roots; Soil; Soil enzymes